DESIGN OF COMPUTER REPAIR SERVICES APPLICATION ANDROID-BASED - Achmad Udin Zailani; Alvino Octaviano; Sholihin, Sholihin (Department of Computer Engineering, Universitas Wiralodra, 2021)
Computers are one form of advances in electronic and informatics technology; the function of the computer itself serves as a tool for writing, drawing, editing images or photographs, or as a means of storage. Android, a Linux-based operating system, is a smart operating system that can compete with operating systems on a computer. Some of the problems identified include user difficulties in overcoming computer damage to determine whether to repair or buy a new unit, difficulty in reaching authorized service providers, risks when deciding to repair at a public service place, and limited access to information and costs repairing computer damage. This research specifically designs an Android application-based computer service application that makes it easier for people to get service services. The above research results formulate computer repair services using an Android-based platform with Android Studio and MySQL as the database for this study. This application is expected to be useful for customers in terms of time and cost.